Risk Factors for Anxiety and Depressive Symptoms in Doctors During the Coronavirus Disease 2019 Pandemic - He, Lanying; Wang, Jian; Zhang, Lijuan; Wang, Feng; Dong, Weiwei; Zhao, Wang (Frontiers in Psychiatry, 2021)
Background: The purpose of our study was to investigate the prevalence of anxiety and depression and its risk factors among doctors during the coronavirus disease (COVID-19) pandemic. Methods: A Hospital-based survey study was conducted. Anxiety was assessed using the Self-Rating Anxiety Scale (SAS), depression was assessed using the Self-Rating Depression Scale (SDS). Multivariable logistic regression was used to analyze data between independent variables with anxiety and depression. Results: A total of 1521 doctors were included, 11.11% (169/1521) of doctors had anxiety, 16.90% (257/1521) had depression. Female [adjusted odds ratio(aOR),1.69; 95% confidence interval (CI), 1.21-2.34; P=0.002], having minor child (aOR, 2.31; 95% CI, 1.50-3.56; P<0.001) were associated with increased risk of anxiety. Female (aOR, 1.56; 95% CI, 1.18-2.06; P=0.002), having minor child (aOR, 1.48; 95% CI, 1.06-2.01; P=0.022) were associated with increased risk of depression. Older age (aOR,0.97; 95% CI, 0.98-0.99; P=0.008) was associated with decreased risk of depression. Conclusions: Anxiety and depression are common mental health problems in doctors during COVID-19 pandemic. We found that female, having minor child, younger age are major risk factors for development of anxiety and depression among doctors.